KONSEP DAN STRATEGI PENGEMBANGAN SMART REGIONAL (SMART CITY) DALAM MENGHADAPI GLOBALISASI VERSION 3.0 DENGAN MENGGUNAKAN METODE PDCA & USEPDSA - Wibowo, Sasono; Gamayanto, Indra (JURNAL LITBANG KOTA PEKALONGAN, 2019)
Smart city is a necessity and no longer a hope, but it has already happened, with the progress of information technology that is increasingly sophisticated and very fast, then changes occur in everyday human life, where humans have united themselves with technology. This journal is a development of two journals - The Future Of IS / IT Strategic Planning In WCC, Australia version 1.0 and the journal analysis of the Wollongong city council using 7s of Galliers and Sutherland methods version 2.0. Furthermore, the focus of this journal - and at the same time the problem is that targets of high quality human resources have not been met; the application of technology and its use; and how the balance between HR and technology can be maintained very well. The results of this journal are the stages that can be carried out by each region in developing human resources and how the technology can help in regional development. It should be understood, that this journal has only reached level 3 (version 3.0), which means this journal is still a basic foundation wi th three stages, and this journal will be continued at the next level (the next version), gradually. Deepening of the supporting journals for this journal and observations and surveys are very important for the completion of information, therefore this journal will continue to be developed until the final stage Keywords: Smart city, Smart regional, Human resources, Technology, Framework